2020
DOI: 10.1088/1748-9326/ab7469
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ecological consequences of forest fires in the continuous permafrost zone of Siberia

Abstract: Wildfires are an important factor in controlling forest ecosystem dynamics across the circumpolar boreal zone. An improved understanding of their direct and indirect, short-to long-term impacts on vegetation cover and permafrost-vegetation coupling is particularly important to predict changes in carbon, nutrient and water cycles under projected climate warming. Here, we apply dendrochronological techniques on a multi-parameter dataset to reconstruct the effect of wildfires on tree growth and seasonal permafros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 72 publications
0
54
0
Order By: Relevance
“…Other studies demonstrated physiological consequences of fire deficits in forests of the western United States [99] and in trees growing on permafrost in boreal ecosystems [100]. All of these studies demonstrated that the responses of the trees, and thus of the stable isotope signature, depend on fire severity.…”
Section: Other Disturbancesmentioning
confidence: 91%
“…Other studies demonstrated physiological consequences of fire deficits in forests of the western United States [99] and in trees growing on permafrost in boreal ecosystems [100]. All of these studies demonstrated that the responses of the trees, and thus of the stable isotope signature, depend on fire severity.…”
Section: Other Disturbancesmentioning
confidence: 91%
“…Along with temperature increases, increasing VPD 14 has been shown to result in low stomatal conductance 3 , thereby responding to water shortage in trees—even in regions affected by permafrost 3 . While water and nutrient supply for plants in the Siberian North predominantly depends on freeze–thaw processes in the active soil layer 16 , 17 , wildfire-induced changes can also significantly affect the active soil layer depth and seasonal dynamics with long-term consequences for carbon, nutrient and water balance of the ecosystem 8 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…These have been shown to curtail surface irradiance and to cause light diffusion (Stine and Huybers, 2014), with the strongest impact over central and eastern Siberia, as well as parts of Alaska and Canada (Briffa et al ., 1998). In addition to the antagonistic role of anthropogenic pollutants, the net primary productivity of the boreal biome is also vulnerable to other abiotic stressors (Beck et al ., 2011; Gauthier et al ., 2015; Girardin et al ., 2016; Charney et al ., 2016), such as the redistribution of nitrogen as a consequence of widespread wildfires that are expected to increase in frequency and intensity under future climate change (Ponomarev et al 2018; Shvetsov et al ., 2019; Knorre et al ., 2019; Kirdyanov et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%